Growth of Porous Platinum Catalyst Structures on Tungsten Oxide Support Materials: A New Design for Electrodes - Hengge, Katharina A.; Heinzl, Christoph; Perchthaler, Markus; Geiger, Simon; Mayrhofer, Karl J. J.; Scheu, Christina (Crystal Growth and Design, 2017)
The growth of a promising material system for high-temperature polymer-electrolyte-membrane fuel cells, namely, platinum (Pt) loaded tungsten suboxide (WO3-x) electrodes, has been studied in-depth. The template-free two-step synthesis results in highly porous three-dimensional networks of crystalline Pt nanorods on the WO3-x support. The formation and growth behavior of these catalyst morphologies are investigated as a function of the deposition time of the catalyst precursor by use of scanning electron microscopy and various transmission electron microscopy techniques. The analysis reveals that octahedral-shaped bulk crystals of the Pt-precursor are formed on the WO3-x support, which subsequently reduce during the thermal treatment. After a reduction time of 4 min, the core of the catalyst morphologies is still bulk material, composed of Pt nanoparticles embedded in a reduced form of the Pt precursor, while the outer shell is formed by a porous network of polycrystalline Pt. Electron tomography helps to reveal the connectivity of the Pt network and allows calculation of the surface area of a 100 nm × 100 nm portion. This is compared to the macroscopic value for the surface area of the samples' entire network obtained by cyclic voltammetry.
CRIS-Team Scopus Importer:2023-03-29